Minding animals : awareness, emotions, and heart - Bekoff, Marc (Oxford University Press, 2002)
Concerned not only with the study of animal behaviour, but also with the innumerable ways in which humans interact with and intrude into the lives of our animal kin. This is a comparative, evolutionary, and ecological work that does not centre on nonhuman primates of one specific group of animals.